Discussion of International Differences in the Timeliness, Conservatism, and Classification of Earnings - Basu, Sudipta (Journal of Accounting Research, 1999)
Sudipta Basu, Discussion of International Differences in the Timeliness, Conservatism, and Classification of Earnings, Journal of Accounting Research, Vol. 37, Studies on Credible Financial Reporting (1999), pp. 89-99